Impact of human milk banking on neonatal mortality, necrotizing enterocolitis, and exclusive breastfeeding – experience from a tertiary care teaching hospital, south India. (19th March 2019) - Adhisivam, B.; Vishnu Bhat, B.; Banupriya, N.; Poorna, Rachel; Plakkal, Nishad; Palanivel, C.
Abstract: Objective: The objective of this study is to study the impact of a Human Milk Bank (HMB) on neonatal mortality, incidence of necrotizing enterocolitis (NEC) and rate of exclusive breastfeeding. Methods: This pre–post intervention study was conducted in a tertiary care teaching institute in south India. Data regarding neonatal mortality, incidence of NEC, and exclusive breastfeeding rates were collected for a period of 6 months before and after establishing a modern HMB and compared. Results: The number of deliveries, live births, and incidence of preterm and VLBW neonates during pre- and post-HMB periods were comparable. Neonatal mortality was 11.32/1000 live births pre-HMB compared with 10.77/1000 live births post HMB. The incidence of NEC was 1.26% of live births pre-HMB compared with 1.07% post-HMB. Exclusive breastfeeding rate pre-HMB was 34% compared with 74% post HMB ( p < .001). Conclusion: There is a decreasing trend in neonatal mortality and incidence of NEC after establishing a HMB. Human milk banking significantly improved exclusive breastfeeding rate in the population studied.